Study on the development and implementation of an interdisciplinary solar panel project to enhance students' interest in STEM - Ahmad Suryadi; Nala Lidya; Hulwah Habibah; Iwan Permana Suwarna (Research and Development in Education (RaDEn), 2024)
This study aimed to develop and implement a STEM education program on solar energy. This study follow Analyze, Design, Develop, Implement, and Evaluate (ADDIE) model. The study was conducted by analysing, designing, and developing a STEM education program consisting of a program guide and a solar panel STEM KIT. The program was implemented in schools involving 83 high school students. The program was implemented in two formats, namely STEM after school and regular learning. Students completed the STEM interest instrument after participating in the STEM education program. The results showed that the program was declared valid for use. In addition, the program implementation results showed no significant difference between students' technology, engineering, mathematics, and STEM career interests in STEM after school and regular STEM classes.  This may be due to several things such as similar content and activities, similar engagement, and similar mentorship. This study implies that the STEM education program can increase students' interest in STEM after-school and regular learning activities.